2020
DOI: 10.1017/cjn.2020.175
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Markers in the Diagnosis of Calcifying Pseudoneoplasm of the Neuraxis

Abstract: Background: Calcifying pseudoneoplasm of the neuraxis (CAPNON) is a rare tumor-like lesion with unknown pathogenesis. It is likely under-reported due to diagnostic challenges including the nonspecific radiographic features, lack of diagnostic markers, and often asymptomatic nature of the lesions. Methods: We performed detailed examination of 11 CAPNON specimens diagnosed by histopathology, with the help of electron microscopy and immunohistochemistry. Results: Electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…They are slow-growing benign lesions presumably attributable to a reactive proliferative process induced by various trigger factors, such as infection, inflammation and injury, and may be possibly associated with inflammatory, degenerative, vascular and neoplastic diseases [2] , [3] , [4] . However, its underlying etiology is still non completely defined and other explanations have been proposed too, including neoplastic process [5] , immune-mediated process [6] , tissue calcinosis [7] , and less likely, metaplastic transformation [8] . Total surgical resection is considered the gold standard of treatment and no additional chemotherapy or radiotherapy is needed [9] , even if some cases of recurrence or local progression after surgery have been described in literature [10] , [11] , [12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are slow-growing benign lesions presumably attributable to a reactive proliferative process induced by various trigger factors, such as infection, inflammation and injury, and may be possibly associated with inflammatory, degenerative, vascular and neoplastic diseases [2] , [3] , [4] . However, its underlying etiology is still non completely defined and other explanations have been proposed too, including neoplastic process [5] , immune-mediated process [6] , tissue calcinosis [7] , and less likely, metaplastic transformation [8] . Total surgical resection is considered the gold standard of treatment and no additional chemotherapy or radiotherapy is needed [9] , even if some cases of recurrence or local progression after surgery have been described in literature [10] , [11] , [12] .…”
Section: Discussionmentioning
confidence: 99%
“…2 In these cases, differential diagnosis may include infectious granulomatous diseases, foreign body reaction and neoplasms such as chordomas, chondro-blastomas, chondrosarcomas and metaplastic meningioma [ 4 , 24 ]. As regards immunohistochemistry, the peripherical palisading cells are positive for epithelial membranous antigen (EMA) and vimentin and are negative for glial fibrillary acidic protein, smooth muscle actin, and S-100 protein, even if the latter has been shown to be positive in some cases [ 6 , 24 ]. Among these, EMA may represent an immunohistochemical marker helpful to distinguish CAPNONs from calcified psammomatous and metaplastic meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…12 Recently, an immunohistochemistry study on 11 CAPNON cases showed that the granular amorphous cores of the CAPNON were positive for neurofilamentlight chain, a cytoplasmic protein expressed in the axons, and there was also evidence of CD8+ cytotoxic T-cells infiltration with a decreased ratio of CD4/CD8 T-cells in the lesions. 30 Based on these findings, they hypothesized that the pathogenesis of CAPNON might be an immunemediated process. 30 Clinical presentation of CAPNON is not specific and depends on its anatomic location, size, local mass effect, and irritation of adjacent tissues.…”
Section: Table 1 (Continued)mentioning
confidence: 99%
“…30 Based on these findings, they hypothesized that the pathogenesis of CAPNON might be an immunemediated process. 30 Clinical presentation of CAPNON is not specific and depends on its anatomic location, size, local mass effect, and irritation of adjacent tissues. Seizures and headache are the most common symptoms of intracranial CAPNON, and pain is most often seen in spinal CAPNON.…”
Section: Table 1 (Continued)mentioning
confidence: 99%
“… 1 4 The clinical presentations of these lesions vary, depending on the location, size, and associated mass effect. 1 5 6 7 8 Although CAPNONs are typically definitively diagnosed histopathologically postresection, 9 radiographic imaging is an important part of the workup. Vasogenic edema is a rare feature on magnetic resonance imaging (MRI), and concurrent perilesional cysts have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%